Characterization of specialised knowledge of the teacher in modeling trigonometric functions in GeoGebra (Encuentros, 2022)
The objective of this research was to characterize the specialized knowledge of the teacher in the modeling of trigonometric functions using the GeoGebra software. For this, with a qualitative approach and with an instrumental case study design, 13 non-participating observation units, a field diary, a questionnaire and a semi-structured interview were carried out with a teacher with training and experience in teaching mathematics mediated by ICT. This research was based on the MTSK model as a theoretical reference, specifically in the subdomains knowledge of the subjects and knowledge of the teaching of mathematics and their respective categories. The main finding was the relationships that exist between the categories of these subdomains with respect to the fact that within the specialized knowledge that the teacher who teaches mathematics must have, there is the in-depth theoretical knowledge of the contents, and then by means of a tool, whose purpose is teaching, as is the case of GeoGebra, to apply these contents of which you already have the knowledge to develop mathematical skills such as modeling.
Keywords: Mathematics teacher; modeling; geogebra; knowledge of mathematics teaching; trigonometric functions; ict